Epidemiology of Congenital Heart Disease in Jinan, China From 2005 to 2020: A Time Trend Analysis - Zhang, Lihua; Liu, Bei; Li, Huimin; Wang, Chengxiang; Yang, Shimin; Li, Zhongliang (Frontiers in Cardiovascular Medicine, 2022)
Background: Although congenital heart defect(CHD) was the dominating birth defect, the time trend analysis of CHD was largely unknown. In our study, the time trend analysis of CHD from 2005 to 2020 in Jinan was conducted, aimed to reveal the epidemiological characteristics in a city and provided the data basis for the goverment to make a policy intervention. Methods: A multi-institutional, retrospective review of CHD for all births from January 1, 2005 to December 31, 2020 was performed. Proportion or prevalence was used to describe the distribution of CHD. Comparisons of CHD characteristics among different groups were assessed with Chi-squares tests. Cochran-Armitage tests(CAT) was used to track changes of CHD prevalence. Results: 322374 births and 5180 CHD in Jinan were included from 2005 to 2020 and the total CHD prevalence was 3.92 per 1000 births. The CHD prevalence showed an upward trend with a total increase of 227.66% from 2005 to 2020. The CHD prevalence in urban areas was 34.17 % higher than that in rural areas，but the gap was narrowing . Atrial septal defect (3.07 per 1000 births), patent ductus arteriosus (1.62 per 1000 births), ventricular septal defect (1.18per 1000 births), tetralogy of Fallot (0.62 per 1000 births), atrioventricular septal defect (0.47 per 1000 births) were the 5 most common subtypes. Conclusion: The prevalence of CHD in Jinan was gradually on the rise, which need to be highly focused by the health management department. Older pregnant women and women in rural areas should be concerned and targeted measures need to be introduced. Key words: Epidemiology, congenital heart disease, prevalence, time trend analysis, causes analysis.